Eastern Roman mounted archers and extraordinary medico-surgical interventions at Paliokastro in Thasos Island during the Protobyzantine period : the historical and medical history records and the archaeo-anthropological evidence - Agelarakis, Anagnostis P., 1956- (Access archaeology., 2020)
A recent archaeological discovery at Paliokastro (Thasos, Greece), and the subsequent study of the human skeletal remains interred in four monumental funerary contexts, provide for the first time through the archaeological record of the region a unique insight of the mounted archers and their female kin during the turbulent ProtoByzantine period.